PENGEMBANGAN PERANGKAT PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI KOMPUTER MATERI ATOM, ION, DAN MOLEKUL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Syahri Syahri; Madlazim Madlazim; Fida Rachmadiarti (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This research aims to produce a feasible guided inquiry instructional materials by using computer simulation to improve students learning achievement of junior high school. The application of computer simulation used consists of PhET (Sims Build an Atom), Jmol, and Periodic Table. Development of this instructional material refers to Dick and Careys model. The subjects of this research was instructional materials that consist of syllabus, lesson plan, students worksheet, textbook, and achievement test. It was conducted to IX grade students in junior high school. The data were collected using questionnaire, observation, and test. The data were analyzed  using descriptive qualitative and quantitative statistic technique. The results of this research reveal that: (1) the instructional materials which is developed categorized very valid; (2) learning implementation categorized very good; (3) cognitive domain of the students learning achievement have increased by a score of N-gain high category; and (4) the students responded positively towards learning. Based on this results, it can be concluded that the guided inquiry instructional materials by using computer simulation which have been developed feasible used to improve students learning achievement.